The Effectiveness of a Primary School Based Badminton Intervention on Children's Fundamental Movement Skills - Michael J. Duncan; Mark Noon; Chelsey Lawson; Josh Hurst; Emma L. J. Eyre (MDPI AG, 2020)
This study examined the effects of the Badminton World Federation (BWF) Shuttle Time program on fundamental movement skills (FMS) in English children. A total of 124 children; 66 in key stage 1 (ages 6−7 years) and 58 in key stage 2 (10−11 years) undertook the Shuttle Time program, once weekly for six weeks (n = 63) or acted as controls (n = 61). Pre, post and ten-weeks post, both process and product FMS were determined. Children in the intervention group, aged 6−7 years, had higher total process FMS (via test of gross motor development-2) compared to the control group at post and ten-weeks post intervention (both p = 0.0001, d = 0.6 and 0.7, respectively). There were no significant differences in process FMS scores for children aged 10−11 years. Ten-meter sprint speed decreased pre to post and was maintained at ten-weeks post for the intervention groups aged 6−7 years (p = 0.0001, d = 0.6) and 10−11 years (p = 0.001, d = 0.2) compared to control. Standing long jump distance increased pre to post (p = 0.0001, d = 0.8) and was maintained at ten-weeks post (p = 0.0001, d = 0.5) for the intervention group. Medicine ball throw performance increased pre to post (p = 0.0001, d = 0.3) for the intervention group. The BWF Shuttle Time program is beneficial in developing FMS for key stage 1 children (ages 6−7).